Interval TpTe Diagnostic Value in Diastolic Dysfunction of Patients with Hypertension - Rano Irmawan; Braghmandaru Adhi Bhaskara; Hasanah Mumpuni; Nahar Taufiq (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Introduction: Diastolic dysfunction has been shown to be associated with an increase in mortality rates in both normal and decreased systolic function. In patients with hypertension, there is elongation of transmural repolarization dispersion in left ventricular, which will cause heart diastolic relaxation disorders. The elongation of the transmural repolarization dispersion is indicated by the increase of the TpTe interval. We conducted this study to fnd out whether the TpTe interval had a good diagnostic value in detecting diastolic dysfunction in patients with hypertension.Methods: This is an analytic observational research using cross sectional design on hypertensive patients in whom echocardiography was performed. The study conducted in February 2017 until March 2017 in Dr. Sarjito general hospital Yogyakarta. Electrocardiography examination was taken after the patient was performed echocardiography. The TpTe interval was calculated using the ‘tail’ method at lead V5. Diastolic dysfunction was established using echocardiographywith the ASE / EAE 2016 algorithm.Results: Of the 112 patients met the criteria of the study subjects. The cut-off value for TpTe was 103.97 m.s., based R.O.C curve analysis. TpTe interval ≥ 103.97 m.s. had a moderate diagnostic value for detecting diastolic dysfunction with 73% accuracy, 83% sensitivity, 64% specifcity, 22% positive predictive value, and 97% negative predictive value. There were 66 (58.9%) subjectswith TpTe interval <103.97 m.s. and 46 subjects (41.1%) with TpTe interval ≥103.97 m.s. There were 12 subjects (10.7%) with diastolic dysfunction. Bivariate and multivariate analyzes showed no demographic and clinical factors that independently affected the TpTe interval.Conclusion: The TpTe interval ≥ 103.97 m.s. had a moderate diagnostic value for detecting diastolic dysfunction in patients with hypertension